The Social Rewards of Online Gambling - Jani Kinnunen (Suomen Antropologi)
Gambling games have been played around the world in most cultures where money has been in use (Binde 2005). The games and the ways of playing them  ave varied over time and space, but the core of gambling is always the same: players place a monetary bet on a possible outcome of some event. It is thus clear that money matters in gambling, but it is not the priority. More bluntly: gambling is not about money.